Factors Influencing the Acceptance of Ferizy E-Ticketing Application Based on UTAUT2 Model - Imam Arizal Razaqi; Anita Wulansari; Rafika Rahmawati (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
The advancement of information technology has accelerated digital transformation in many sectors, including maritime transportation. One notable result of this transformation is the development of the Ferizy application, an online ticket booking platform introduced by PT ASDP Indonesia Ferry. Despite its innovation, users continue to encounter technical challenges and insufficient access to information. User feedback has highlighted issues such as incomplete information and booking process errors. This research aims to explore the factors influencing the acceptance of the Ferizy application by applying a modified UTAUT2 model. The study incorporates two additional variables, Trust and Word of Mouth, into the UTAUT2 framework. A quantitative research methodology was employed, using SEM-PLS analysis on initial data collected from 522 Ferizy users, which was later refined to 442 valid responses. The analysis demonstrated that Word of Mouth and Price Value have a significant impact on users' Behavioral Intention, which, in turn, strongly influences actual Use Behavior. On the other hand, variables such as Effort Expectancy, Facilitating Conditions, Performance Expectancy, Social Influence, and Trust were found to have no significant effect on Behavioral Intention. These results offer valuable insights for both users and developers, enhancing the understanding of the factors that influence the acceptance of the Ferizy platform.